The HMG-CoA Reductase Inhibitor Activities of Soy Protein Hydrolysates from Papain Hydrolysis - Sandra Hermanto; Aldi Octavio; Azrifitria Azrifitria; Susi Kusumaningrum (Universitas Jenderal Soedirman, 2021)
The search for an HMG-CoA reductase inhibitor agent as a safe and inexpensive alternative treatment for hypercholesterolemia has been carried out using soy protein hydrolysates as one of the bioactive peptide sources. This study was conducted to explore the potency of soy protein hydrolysates as an anti hypercholesterolemia agent by an in vitro assay, through the inhibition capacity of the HMG-CoA (3-hydroxy-3-methyl glutaryl-coenzyme A) reductase enzyme as a key component of cholesterol biosynthesis. Sample preparation started with soy protein isolation through acid precipitation and separated by centrifugation. The samples were analyzed the proximate content and hydrolyzed by papain enzyme at concentration 0.2% (w/v), for 0-6 hours and at 37, 50, and 55 oC. The protein hydrolysates were subsequently evaluated for hydrolysis degree (% DH), hydrolysates profile with SDS-PAGE (Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis), and anti-cholesterol assay through HMG-CoA reductase inhibition tests. The sample with the highest inhibition activity was fractionated using gel filtration chromatography (Sephadex G-10) and the molecular weight of fractions was characterized by LCMS QTOF (Liquid Chromatography-Mass Spectrometry Quadrupole Time-of-Flight) for molecular weight determination. The results indicated the optimum hydrolysis conditions of soy protein isolates were obtained at 3 hours incubation, at 50 °C with DH 33.39% and the inhibition value was 95.65% (protein concentration 39.21 μg / mL). LCMS data showed the molecular weight of fractionated peptides were 1514 and 2029 Da. We assumed that both peptides have the same affinity as previous peptides in inhibiting HMG-CoA reductase.